Fact-finding without facts the uncertain evidentiary foundations of international criminal convictions - Combs, Nancy A. 1965- (Cambridge University Press, 2010)
"This book explores international criminal fact-finding to reveal that criminal trials are beset by impediments that impair their ability to determine who did what to whom"--Provided by publisher.